Chapter 2: Decoupling and redistribution in realising the Sustainable Development Goals - Lerpold, Lin (Edward Elgar Publishing, 2023)
Climate, environment and social sustainability are most often theorised and empirically depicted as separate challenges. We explore the interdependence and trade-offs between the goals and suggest that decoupling must have a more prominent focus. Unlike the rapidly expanding body of quantitative goal and target correlation studies, we focus on the underlying conceptual issues. The SDGs focusing on social goals are correlated with economic growth and SDG 8 in a positive way. At the same time, increased climate emissions and ecological footprint are negatively correlated with economic growth and SDG 8. If the social goals are to be met, economic growth must continue but without it increasing the planetary footprint of humankind in the natural world. For now, at least, evidence of such needed decoupling continues to be patchy at best. We conclude with a discussion of redistribution as a possible solution.